LINC00265 targets miR-382-5p to regulate SAT1, VAV3 and angiogenesis in osteosarcoma - Xiao, Ying (Aging (Albany NY), 2020)
We explored the mechanism by which LINC00265 regulates angiogenesis of osteosarcoma cells via the miR-382-5p/spermidine/spermine N1-acetyltransferase-1 (SAT1) and miR-382-5p/vav guanine nucleotide exchange factor 3 (VAV3) axis. Cell scratch assay, Transwell assay and tube formation assay were applied to detect cell migration, invasion and tube formation abilities. The effects of LINC00265 targeting miR-382-5p in osteosarcoma in vivo were studied using a tumour-burden assay. A total of 70 genes potentially involved in osteosarcoma angiogenesis were identified, and a Gene Ontology (GO) analysis found that SAT1 and VAV3 were closely related to angiogenesis. Bioinformatics analysis and clinical experiments confirmed that LINC00265, SAT1 and VAV3 were overexpressed in osteosarcoma and related to a poor prognosis, whereas miR-382-5p was downregulated and associated with a poor prognosis. It was confirmed that LINC00265 promoted the proliferation, migration, invasion and angiogenesis of osteosarcoma cells by targeting miR-382-5p to mediate SAT1 and VAV3. Collectively, LINC00265 might promote proliferation, migration, invasion and angiogenesis by targeting miR-382-5p/SAT1 and miR-382-5p/VAV3 in osteosarcoma.